2005
DOI: 10.1186/1471-2202-6-36
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal lesions facilitate instrumental learning with delayed reinforcement but induce impulsive choice in rats

Abstract: Background: Animals must frequently act to influence the world even when the reinforcing outcomes of their actions are delayed. Learning with action-outcome delays is a complex problem, and little is known of the neural mechanisms that bridge such delays. When outcomes are delayed, they may be attributed to (or associated with) the action that caused them, or mistakenly attributed to other stimuli, such as the environmental context. Consequently, animals that are poor at forming context-outcome associations mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(63 citation statements)
references
References 120 publications
4
59
0
Order By: Relevance
“…Even with a 64-s delay of reinforcement, rats were able to acquire instrumental behavior which became manifest as a result of this context extinction treatment. These results are consistent with those of Cheung and Cardinal (2005) who observed that hippocampal lesions had opposite effects in instrumental acquisition depending on whether the reinforcer was presented immediately after lever pressing, or delayed by 10 or 20 s. That is, they conducted complete (or sham) hippocampal lesions before they administered instrumental training with 0-, 10-, and 20-s delays of reinforcement. Relative to their sham controls, hippocampal rats showed retarded instrumental responding when the reinforcer was presented immediately (0-s delay; a result similar to that of Pearce & Hall, 1978, after context extinction), but stronger responding when the reinforcer was delayed for 20 s (consistent with the context extinction results of Reed & Reilly, 1990, and Dickinson et al, 1992).…”
Section: The Role Of Contiguitysupporting
confidence: 91%
See 1 more Smart Citation
“…Even with a 64-s delay of reinforcement, rats were able to acquire instrumental behavior which became manifest as a result of this context extinction treatment. These results are consistent with those of Cheung and Cardinal (2005) who observed that hippocampal lesions had opposite effects in instrumental acquisition depending on whether the reinforcer was presented immediately after lever pressing, or delayed by 10 or 20 s. That is, they conducted complete (or sham) hippocampal lesions before they administered instrumental training with 0-, 10-, and 20-s delays of reinforcement. Relative to their sham controls, hippocampal rats showed retarded instrumental responding when the reinforcer was presented immediately (0-s delay; a result similar to that of Pearce & Hall, 1978, after context extinction), but stronger responding when the reinforcer was delayed for 20 s (consistent with the context extinction results of Reed & Reilly, 1990, and Dickinson et al, 1992).…”
Section: The Role Of Contiguitysupporting
confidence: 91%
“…Contiguity plays a role in instrumental behavior, as decreases in instrumental behavior are typically observed when delays are imposed between target responses and reinforcement, a finding that has been observed in both rats (e.g., Cheung & Cardinal, 2005; Dickinson, Watt, & Griffiths, 1992) and humans (e.g., Shanks & Dickinson, 1991). An issue here is what role, if any, response-reinforcer contiguity plays in the way in which contexts influence instrumental behavior.…”
Section: The Role Of Contiguitymentioning
confidence: 97%
“…Whilst hippocampal regions were not initially hypothesized to be involved in the attentional tasks, research in animals has found that lesions to the hippocampus can induce impulsive behavior (Cheung & Cerdinal, 2005l; Mariano et al, 2009), possibly due to hippocampal connections with the nucleus accumbens (Pattij & Vanderschuren, 2008). Amygdala dysfunction has also been implicated in impulsive or poor decision-making (Bechara et al, 1999; Matsuo et al, 2009), although Matsuo and colleagues (2009) did not find an association between amygdalar gray-matter volume and BIS-11 scores.…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen mice were randomly assigned to the sham control group (sham, n ¼ 6) and the DH lesion group ( pre-DH, n ¼ 9). Surgeries were performed after mice were shaped to press the lever for food pellets in order to exclude any effect that DH lesions might have on instrumental learning per se [50,51]. After mice recovered from surgery, they were trained with the bi-peak procedure as described in §2d(iii).…”
Section: (B) Surgerymentioning
confidence: 99%